Historiografía regional y el Bicentenario de la Independencia - Zubieta Núñez, Filomeno (2021)
The commemoration of 200 years of national independence as a republic invites us, among other actions, to look at the historiographic production about this process, especially in the provinces. What have we done, and what are we doing in our inland provinces to understand and recognize their ancestors’ participation in the national independence process? This research offers a balanced review of historical publications related to independence from the last years. We took the so-called Norte Chico as a geographical reference area, which includes the provinces of Barranca, Huaura, Huaral (the former Chancay province) in the department of Lima.